A concise route to MK-4482 (EIDD-2801) from cytidine. Issue 87 (8th October 2020) - Vasudevan, N.; Ahlqvist, Grace P.; McGeough, Catherine P.; Paymode, Dinesh J.; Cardoso, Flavio S. P.; Lucas, Tobias; Dietz, Jule-Phillip; Opatz, Till; Jamison, Timothy F.; Gupton, Frank B.; Snead, David R.
Abstract : A two-step route to MK-4482 (EIDD-2801, 1) was developed consisting of an esterification and hydroxamination of cytidine. Abstract : A two-step route to MK-4482 (EIDD-2801, 1 ) was developed consisting of an esterification and hydroxamination of cytidine. The selective acylation and direct amination eliminate the need for protecting and activating groups and proceed in overall yield of 75%, a significant advancement over the reported yield of 17%. The step count is reduced from five transformations to two, and expensive uridine is replaced with the more available cytidine.